Modulating the luminance of organic light-emitting diodes via optical stimulation of a photochromic molecular monolayer at transparent oxide electrode. Issue 9 (21st February 2020) - Ligorio, Giovanni; Cotella, Giovanni F.; Bonasera, Aurelio; Zorn Morales, Nicolas; Carnicella, Giuseppe; Kobin, Björn; Wang, Qiankun; Koch, Norbert; Hecht, Stefan; List-Kratochvil, Emil J. W.; Cacialli, Franco
Abstract : Molecular switches reversibly change isomeric configuration upon external stimuli. Chemically bound monolayer on electrodes can allow for adding multifunctionality to devices. As a proof-of-concept this approach is employed in a light emitting diode. Abstract : Self-assembled monolayers (SAMs) deposited on bottom electrodes are commonly used to tune charge carrier injection or blocking in optoelectronic devices. Beside the enhancement of device performance, the fabrication of multifunctional devices in which the output can be modulated by multiple external stimuli remains a challenging target. In this work, we report the functionalization of an indium tin oxide (ITO) electrode with a SAM of a diarylethene derivative designed for optically control the electronic properties. Following the demonstration of dense SAM formation and its photochromic activity, as a proof-of-principle, an organic light-emitting diode (OLED) embedding the light-responsive SAM-covered electrode was fabricated and characterized. Optically addressing the two-terminal device by irradiation with ultraviolet light doubles the electroluminescence. The original value can be restored reversibly by irradiation with visible light. This expanded functionality is based on the photoinduced modulation of the electronic structure of the diarylethene isomers, which impact the charge carriers' confinement within the emissive layer. This approach could be successfully exploited in the field of opto-communication technology, for example to fabricate opto-electronic logic circuits.